Studies on the enhancement of plant regeneration frequency in Brassica napus in vitro culture - TANG Gui-xiang; ZHOU Wei-jun (浙江大学学报. 农业与生命科学版)
The effects of different explants, genotypes, Ag+ and GA, on in vitro regeneration were studied in Brassica napus L. High shoot regeneration frequencies were obtained from the 4-day old cotyledon explants of various genotypes in MS medium added with BA 3.0 mg/L, NAA 0.15 mg/L, GA3 1.00 mg/L, and AgNO3 2.5 mg/L, and cultured for 27 days at 23-25℃ and 16 h day length (2 000～3 000 lx).